(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
This study explores the motivations and struggles experienced by hospitality graduates who embark on entrepreneurial journeys in Nepal. Employing a narrative inquiry approach, the study examines the lived experiences of four hotel management graduates from the Nepal Academy of Tourism and Hotel Management (NATHM). The study reveals two distinct motivation layers: the initial excitement driven by academic exposure and the persistent inspiration from external sources such as mentors, internships, and personal aspirations. However, significant barriers, including financial constraints, limited institutional support, and a lack of enabling policies, hinder entrepreneurial efforts. Graduates also cited cultural and familial expectations as critical influences on their career choices. This study highlights the duality of challenges and opportunities within Nepal’s hospitality education and entrepreneurial ecosystem. The study recommends policy interventions, enhanced institutional frameworks, and targeted entrepreneurial education to support aspiring entrepreneurs. These findings contribute to the broader discourse on aligning hospitality education with the evolving demands of a dynamic global industry, offering valuable insights for educators, policymakers, and industry practitioners.